The Role of Artificial Intelligence in Enhancing Organizational Procurement Productivity: A Systematic Literature Review - Oskar Ezra Alan Muin; M.M. Lanny W. Pandjaitan; Lukas Lukas (Publikasi Indonesia, 2026)
Digital transformation is driving significant changes in various organizational functions, including in the procurement process. Traditional procurement processes still often rely on manual activities and limited data analysis that can hinder organizational productivity. This study aims to analyze the role of Artificial Intelligence (AI) in increasing procurement productivity through the use of data analysis and procurement process automation. The research method used is a literature study by examining various studies related to the implementation of AI in Procurement and supply chain management published in the period 2020–2026. The results of the study show that AI technology such as machine learning, predictive analytics, and intelligent automation is able to improve the efficiency of the procurement process through predicting needs, automatic supplier evaluation, and data-based decision-making. AI implementation also contributes to reducing human error, increasing transparency, and accelerating the procurement cycle. Thus, the integration of AI in the Procurement system can increase organizational productivity and support digital transformation in supply chain management.